Bleach. 11, A star and a stray dog - Kubo, Tite (Kubo, Tite. Bleach (VIZ Media) ;, 2006)
Ichigo defeats Ikkaku and discovers where Rukia is being detained before her execution. Meanwhile, Ganju is having more difficulty with his opponent, and Uryû finally has an opportunity to prove how much more powerful he has become.